Comparison of phosgene, chlorine, and hydrogen chloride as reagents for converting molten CaO. CaCl/sub 2/ to CaCl/sub 2 - Fife, K. W. (Los Alamos National Laboratory, 1985)
One method at Los Alamos for preparing impure plutonium metal from the impure oxide is by batch reduction with calcium metal at 850/sup 0/C in a CaCl/sub 2/ solvent. The solvent salt from this reduction is currently discarded as low-level radioactivity waste only because it is saturated with the CaO byproduct. We have demonstrated a pyrochemical technique for converting the CaO to CaCl/sub 2/ thereby incorporating solvent recycling into the batch reduction process. We will discuss the effectiveness of HCl, Cl/sub 2/, and COCl/sub 2/ as chlorinating agents and recycling actual spent process solvent salts. 6 refs., 8 figs.